Variation in Germination Traits of Jatropha Curcas at Stand and Tree Levels in Laboratory and Nursery Conditions - Malhotra, Kshitij; Pandey, Vidyadhar; Kumar, Dinesh (Indian Forester, 2013)
Seed germination traits i.e. germination percent, germination value and germination energy in laboratory and nursery conditions were evaluated for 97 accessions of Jatropha curcas belonging to 10 stands in Uttarakhand. On the basis of all seed germination traits tree T1 of stand S6 and tree T1 of stand S8 were best. Stand S3, which was not the best stand for germination percentage on the basis of stand level analysis, had three trees showing 86 percent laboratory germination on par with the trees having the highest germination percent (87.5%) in the study at tree level. High heritability (77%) and moderate genetic gain (21%) were recorded at stand level for germination percent at 5% selection intensity. The expression of germination traits was usually higher under laboratory than under nursery conditions. It was suggested that the collection of seeds for germination purpose should be done by taking individual tree as a unit ratherthan taking standas unit of collection.